2020
DOI: 10.1002/pen.25506
|View full text |Cite
|
Sign up to set email alerts
|

Natural compounds from Punica granatum peel as multiple stabilizers for polyethylene

Abstract: Punica granatum peel extractive (PPE), a novel stabilizer of polyethylene, is investigated in this study. Oxidation onset temperature (OOT), carbonyl index (CI), melt flow rate (MFR), tensile strength, and elongation at break are used to characterize the effects of PPE, which are also compared with commercial antioxidant (Irganox 1010) with the presence of tetrakis (2,4-di-tert-butylphenol) [1,1-biphenyl]-4,4 0-diylbisphosphite (PEPQ). Long-term and short-term aging results show that samples modified by PPE or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
(89 reference statements)
0
16
0
Order By: Relevance
“…Previous results unambiguously show that pomegranate peel extract is a potential stabilizer for polymers [ 20 , 21 ]. However, as mentioned above, the existing information is insufficient and contradictory; further research is needed to establish the full potential of the substance.…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…Previous results unambiguously show that pomegranate peel extract is a potential stabilizer for polymers [ 20 , 21 ]. However, as mentioned above, the existing information is insufficient and contradictory; further research is needed to establish the full potential of the substance.…”
Section: Introductionmentioning
confidence: 63%
“…As mentioned earlier, only two reports are available on the effect of pomegranate extract on the stabilization of PE, according to our knowledge. Xia et al [ 20 ] used an ethanol extract and found it to be an excellent overall stabilizer, including processing, oxidative, and light stabilization. They used the extract at 0.12 and 0.7 wt% with and without a secondary antioxidant, PEPQ, and compared the effect to that of 0.12 wt% of Irganox 1010.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations